2010
DOI: 10.1002/jbmr.257
|View full text |Cite
|
Sign up to set email alerts
|

Osteoporosis in COPD outpatients based on bone mineral density and vertebral fractures

Abstract: One of the extrapulmonary effects of chronic obstructive pulmonary disease (COPD) is osteoporosis. Osteoporosis is characterized by a low bone mineral density (BMD) and microarchitectural deterioration. Most studies in COPD patients use dual-energy X-ray absorptiometry (DXA) only to determine osteoporosis; therefore, microarchitectural changes without a low BMD are missed. The aim of this study was to determine the prevalence and correlates of osteoporosis in COPD patients based on DXA, spinal X-rays, and comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
93
0
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 102 publications
(103 citation statements)
references
References 46 publications
5
93
0
5
Order By: Relevance
“…Although fractures have a higher incidence in osteoporotic patients than those with osteopenia, the majority of low-impact fractures occur in people with osteopenia [79] and therefore it may be prudent to intervene at less severe levels of bone density than is currently standard practice. Vertebral fractures are common in COPD [80] and lead to significant decrements in lung function from extrathoracic restriction and pain.…”
Section: Low Bone Mineral Density and Fracture Riskmentioning
confidence: 99%
“…Although fractures have a higher incidence in osteoporotic patients than those with osteopenia, the majority of low-impact fractures occur in people with osteopenia [79] and therefore it may be prudent to intervene at less severe levels of bone density than is currently standard practice. Vertebral fractures are common in COPD [80] and lead to significant decrements in lung function from extrathoracic restriction and pain.…”
Section: Low Bone Mineral Density and Fracture Riskmentioning
confidence: 99%
“…Interestingly, some studies have shown COPD patients were prone to be vitamin D deficient [20][21][22]. In one study using a vitamin D serum threshold of <80 nmol/L, 86% of COPD subjects were found to be deficient [11], and in another study using a cutoff of <50 nmol/L in age-matched smoking controls, 43%,53%, and 76%, mild-, moderate-and severe COPD patients were vitamin D deficient respectively [23]. In reverse, vitamin D deficiency may contribute to poor lung function although the mechanism is still a bit unclear [23], and some authors simply see vitamin D deficiency and COPD as in a vicious cycle [22] (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported a prevalence of OP-COPD dual diagnosis that varies from 4-60% [11][12][13][14][15], depending on the type of measurements used and the severity of COPD. This relationship is thought to be a result of risk factors that are shared by both OP and COPD: e.g., age, smoking, low BMI and steroid use.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently exercise intolerance may render activities of daily life problematic, leading to a downward spiral in which there is a progressive reduction in physical activity [3][4][5][6][7][8]. Thus, individuals with COPD can end up in a vicious circle of physical deconditioning, including loss of lower limb muscle mass and strength, loss of balance and osteoporosis [8][9][10][11].In the past 20 years, pulmonary rehabilitation has become an integrated part of the management of individuals with moderate to very severe COPD [12,13]. Pulmonary rehabilitation, defined as an evidence-based, multidisciplinary and comprehensive intervention for patients with chronic respiratory diseases who are symptomatic and often have decreased daily life activities, is designed to reduce symptoms, optimise functional status and increase participation in activities of daily living [14].…”
mentioning
confidence: 99%